2023
DOI: 10.14309/ajg.0000000000002499
|View full text |Cite
|
Sign up to set email alerts
|

Conventional vs Short Duration of Antibiotics in Patients With Moderate or Severe Cholangitis: Noninferiority Randomized Trial

Deshidi Srinu,
Jimil Shah,
Anuraag Jena
et al.

Abstract: Background: Successful biliary drainage and antibiotics are the mainstays of therapy in management of patients with acute cholangitis. However, the duration of antibiotic therapy after successful biliary drainage has not been prospectively evaluated. We conducted a single centre, randomized, non-inferiority trial to compare short and conventional duration of antibiotic therapy in patients with moderate or severe cholangitis. Methods: Consecutive patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
8
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 24 publications
(36 reference statements)
0
8
0
Order By: Relevance
“…Clinical cure was defined as the absence of initial presenting symptoms by day 14 after biliary drainage, coupled with no recurrence or death by day 30. 24 , 25 Recurrence was defined as the initiation of a new antibiotic therapy for recurrent cholangitis, subsequent infection in the hepatic–pancreatic–biliary region, or any other subsequent infection possibly related to the initial episode of cholangitis. 5 , 26 , 27 …”
Section: Methodsmentioning
confidence: 99%
“…Clinical cure was defined as the absence of initial presenting symptoms by day 14 after biliary drainage, coupled with no recurrence or death by day 30. 24 , 25 Recurrence was defined as the initiation of a new antibiotic therapy for recurrent cholangitis, subsequent infection in the hepatic–pancreatic–biliary region, or any other subsequent infection possibly related to the initial episode of cholangitis. 5 , 26 , 27 …”
Section: Methodsmentioning
confidence: 99%
“…In the STOP-IT trial, for patients with severe or complicated intra-abdominal infections who received adequate source control, antibiotics were continued for a fixed duration (4 days) or for 2 days after resolution of signs of infection (total of 8 to 10 days). Patients treated with shorter fixed-durations of antibiotics had similar clinical cure rates to those treated with more prolonged durations [ 27 , 28 ]. The DURAPOP trial of critically ill patients with intra-abdominal infections similarly showed that shorter courses of antibiotics (8 versus 15 days) were associated with more antibiotic-free days while maintaining similar rates of mortality and length of stay [ 29 ].…”
Section: Three Approaches To Determining When To Stop Antibioticsmentioning
confidence: 99%
“…I read with interest the noninferiority randomized controlled trial by Srinu et al (1), which compared 4- and 8-day treatments of moderate-to-severe acute cholangitis. The authors concluded that the short duration (SD) treatment group was noninferior to the conventional duration (CD) group for the primary outcome, clinical cure; however, I do not think they can conclude that from the results.…”
mentioning
confidence: 99%